SARS-CoV-2 Spike-specific IFN-γ T-cell Response After COVID-19 Vaccination in Patients With Chronic Kidney Disease, on Dialysis, or Living With a Kidney Transplant. Issue 11 (18th October 2022) - Imhof, Céline; Messchendorp, A. Lianne; van der Heiden, Marieke; Baan, Carla C.; van der Molen, Renate G.; Remmerswaal, Ester B. M.; de Vries, Rory D.; Diavatopoulos, Dimitri A.; Boerma, Annemarie; Bakker, Femke J.; Oosterhout, Emily; Bemelman, Frederike J.; et al.
Abstract : Background: Studies have shown that coronavirus disease 2019 (COVID-19) vaccination is associated with a lower humoral response in vulnerable kidney patients. Here, we investigated the T-cell response following COVID-19 vaccination in kidney patients compared with controls. Methods: Patients with chronic kidney disease (CKD) stage G4/5 [estimated glomerular filtration rate <30 mL/min/1.73 m2], on dialysis, or living with a kidney transplant and controls received 2 doses of the mRNA-1273 COVID-19 vaccine. Peripheral blood mononuclear cells were isolated at baseline and 28 d after the second vaccination. In 398 participants (50% of entire cohort; controls n = 95, CKD G4/5 n = 81, dialysis n = 78, kidney transplant recipients [KTRs] n = 144)‚ SARS-CoV-2-specific T cells were measured using an IFN-γ enzyme-linked immune absorbent spot assay. Results: A significantly lower SARS-CoV-2-specific T-cell response was observed after vaccination of patients on dialysis (54.5%) and KTRs (42.6%) in contrast to CDK G4/5 (70%) compared with controls (76%). The use of calcineurin inhibitors was associated with a low T-cell response in KTRs. In a subset of 20 KTRs, we observed waning of the cellular response 6 mo after the second vaccination, which was boosted to some extent after a third vaccination, although T-cell levels remained low. Conclusion: Our data suggest that vaccination is less effective in these patient groups, with humoral nonresponders also failing to mount an adequate cellular response, even after the third vaccination. Given the important role of T cells in protection against disease and cross-reactivity to SARS-CoV-2 variants, alternative vaccination strategies are urgently needed in these high-risk patient groups. Abstract :